BoLA - DRB3 Gene Polymorphism and its Association with Lactation Yield and Milk Constituents in Crossbred Cattle - Tayeng, Kauvery; Tomar, Satyendra Singh; Nanavat, Sandeep; Aich, Ranjit; Ignetious, Shely; Nagoriya, Sunil Kumar (Indian Journal of Veterinary Sciences and Biotechnology, 2021)
The present study was undertaken to explore polymorphism at exon 2 of BoLA-DRB3 gene locus and its association with milk yield, fat% and protein % in a total of 40 Holstein-Friesian crosssbred cows using PCR-RFLP method. PCR-RFLP using Hae III restriction enzymerevealed presence of 7 genotypes with frequencies 0.475 (AA), 0.225 (AB), 0.050 (AE), 0.100 (BB), 0.050 (DD), 0.050 (EE) and 0.050 (II),respectively and PCR-RFLP using Bst YI yielded 3 genotypes with frequencies 0.050 (AA), 0.625 (AB) and 0.325 (BB), respectively. To studythe association of BoLA-DRB3.2 genotypes with milk yield, fat and protein %, the data was subjected to analysis of variance employinggeneral linear model using SPSS software package. Effect of farm (p
Keywords: BoLA-DRB3; Crossbred Cows; Fat %; , Lactation yield; PCR-RFLP; Protein %.